THE POTENTIAL OF TOMATOES AND SPINACH AS A DIVERSIFICATION OF PROCESSED FOOD FOR KWT KARYA BUNDA MAESAN - Maria Belgis; Yuli Witono; Ardiyan Dwi Masahid; Ahmad Nafi’; Livia Wahyuni; Lailatul Azkiyah (UNEJ e-Proceeding, 2022)
Maesan is one of the sub-districts in Bondowoso Regency, where people primarily work in agriculture. In Maesan sub-district, there is a KWT (Farmer Women's Group) Karya Bunda, which does not have superior products processed tomatoes or spinach. Maesan people use tomatoes and spinach as daily vegetables. The availability of tomatoes and spinach in Maesan is relatively abundant. If the harvest is large, the price of tomatoes is meager, so they are not harvested by farmers and suffer heavy losses. One of the diversions of processed food is tomato sauce and spinach chips. KWT Karya Bunda has never used tomatoes and spinach as diversified products. So it is necessary to socialize and train how to produce tomato sauce and spinach chips. Moreover, test the favorability of tomato sauce and spinach chips. We hope it can be developed and impact KWT Karya Bunda's income. 34 participants of KWT Karya Bunda attended the socialization activity. The socialization activity consisted of presenting post-harvest technology material and how to make tomato sauce and spinach chips, making tomato sauce and spinach chips and filling out a sensory questionnaire (liking) for spinach sauce and chips with a google form. The participants of KWT Karya Bunda were very enthusiastic about making tomato sauce and spinach chips. The results of sensory data showed that 79.4% very liked tomato sauce, and 20.6% liked tomato sauce. Meanwhile, the sensory assessment of spinach chips was 64.7% very like and 35.3% like. This shows that both products have the potential to be developed as KWT's main products. Keywords: maesan, KWR Karya Bunda, tomato sauce, spinach chips